Contrasting effects of d-methamphetamine, 3,4-methylenedioxymethamphetamine, 3,4-methylenedioxypyrovalerone, and 4-methylmethcathinone on wheel activity in rats - Huang, Pai-Kai (2012)
BACKGROUND: Reports from US, UK and European drug policy entities, and ongoing media accounts, show increasing recreational use of 4-methylmethcathinone (4-MMC, mephedrone) and 3,4-methylenedioxypyrovalerone (MDPV). Severe sympathomimetic symptoms, hallucinations, psychoses, and even deaths have been reported, yet little scientific information is available on the effects of these compounds in laboratory models. Available studies on the neurochemistry of these drugs show that 4-MMC and MDPV enhance DA neurotransmission, while 4-MMC additionally enhances 5-HT neurotransmission- a pattern much like that reported for methamphetamine vs. 3,4-methylenedioxymethamphetamine (MDMA). As is the case for designer amphetamines, these neurochemical distinctions may predict differential potential for repetitive versus episodic abuse and distinct lasting toxicities. METHODS: This study determined relative locomotor stimulant effects of 4-MMC (1–10 mg/kg, s.c.) and MDPV (0.5–5.6 mg/kg, s.c.), in comparison with d-methamphetamine (MA; 0.5–5.6 mg/kg, s.c.) and MDMA (1–7.5 mg/kg, s.c.) on a measure of locomotor activity – voluntary wheel running – in male Wistar rats (N=8). RESULTS: Compared to counts of wheel rotations after saline, a biphasic change in the pattern of counts was observed after injections of MA and MDPV, with relatively higher counts following lower doses and lower counts following the highest dose. However, monophasic, dose-dependent reductions in counts were observed in response to injections of MDMA and 4-MMC. CONCLUSION: Thus, voluntary wheel running yielded the same categorical distinctions for these drugs as did prior experiments testing the effects of these drugs on monoaminergic neurotransmission. These data indicate that MDPV produces prototypical locomotor stimulant effects whereas 4-MMC is more similar to the entactogen MDMA.